2018
DOI: 10.1021/acs.cgd.8b01527
|View full text |Cite
|
Sign up to set email alerts
|

Cu(I)-Based Metal–Organic Frameworks as Efficient and Recyclable Heterogeneous Catalysts for Aqueous-Medium C–H Oxidation

Abstract: The enantioselective transformation of ubiquitous C–H bonds into valuable CO bonds offers an efficient synthetic approach to construct carbonyl functionalized molecules. However, the grand obstacles in the reaction are the selectivity issues and side reactions under the harsh reaction conditions. In order to overcome the limits, two Cu­(I)-based MOFs {(NEt4)0.5[Cu3(TTPB)0.75(CN)0.5(H2O)]·H2O} n (1) and {[Cu2(TTPB)0.5]·DMF·2H2O} n (2) were synthesized (H4TTPB = 5,5′-(4′,5′-bis­(4-(1H-tetrazol-5-yl)­phenyl)-[… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…The product (59 mg, 89% yield) was isolated by eluant EtOAc/PE (1:9) as yellow liquid. The spectra match the reported literature [28] . This article is protected by copyright.…”
Section: Accepted Manuscriptsupporting
confidence: 89%
“…The product (59 mg, 89% yield) was isolated by eluant EtOAc/PE (1:9) as yellow liquid. The spectra match the reported literature [28] . This article is protected by copyright.…”
Section: Accepted Manuscriptsupporting
confidence: 89%
“…XPS of the blue samples showed that the high‐resolution Cu 2p spectrum in 3 can be spilt to four peaks, i. e., 962.9, 954.0, 943.4 and 934.1 eV, which are characteristics of divalent copper (Figure 1b). The peaks of 962.9 and 943.4 eV are satellite peaks of Cu 2p 1/2 (954.0 eV) and Cu 2p 3/2 (934.1 eV) [7b,9] . In contrast, XPS of Cu I −MOF 1 displays the binding energy peaks of 951.8 eV (Cu 2p 1/2 ) and 932.0 eV (Cu 2p 3/2 ), indicating Cu I chemical state.…”
Section: Figurementioning
confidence: 97%
“…By virtue of abundant N atoms as Lewis basic sites in the framework, MOF 2 can be investigated and implemented to catalyze the Knoevenagel condensation reaction. The prepared block crystals were soaked in fresh toluene for 30 min and further dried in air for 2 h. In a typical reaction, malononitrile (1.1 mol) and substrates with various functional groups (1.0 mmol) were dissolved in 6 mL of toluene in the presence of MOF 2 (100 mg), which was continually heated at 80 °C for 4 h under slow stirring. The catalytic resultant was measured and calculated by the GC method.…”
Section: Resultsmentioning
confidence: 99%